2006
DOI: 10.1161/01.str.0000241064.46659.69
|View full text |Cite
|
Sign up to set email alerts
|

Transesophageal Echocardiography Is Superior to Transthoracic Echocardiography in Management of Patients of Any Age With Transient Ischemic Attack or Stroke

Abstract: Background and Purpose-The merits of transthoracic echocardiography (TTE) and transesophageal echocardiography (TEE) in the management of transient ischemic attack (TIA) and stroke patients remains matter of debate. Methods-Two hundred and thirty-one consecutive patients with a recent TIA or stroke for which no definite cause and indication for anticoagulation was assessed after standardized work-up underwent TTE and TEE. Echocardiographic findings were categorized into minor and major risk factors. Results-A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
159
7
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(175 citation statements)
references
References 17 publications
7
159
7
2
Order By: Relevance
“…It is well known that TEE is one of the most useful tools and the gold standard for detecting potential sources of embolism from the heart and aorta 6) . In our TEE findings, LAA slow flow velocity was the most common one, SEC second and PFO third.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that TEE is one of the most useful tools and the gold standard for detecting potential sources of embolism from the heart and aorta 6) . In our TEE findings, LAA slow flow velocity was the most common one, SEC second and PFO third.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that atrial fibrillation (AF), which causes left atrial thrombus (LAT) that may produce an embolism, is a common cause of ischemic stroke, and that AF -related strokes are accompanied by severe neurological deficits, disability and high mortality 5) . 6) .…”
Section: Introductionmentioning
confidence: 99%
“…Some authors found that TEE is superior in detecting left atrial appendage and aortic atheroma pathology. 13 On the other hand, meta-analyses showed high interstudy variation in the definition and prevalence of common findings (including left atrial thrombus, aortic atheroma, and patent foramen ovale) between studies of similar populations. Moreover, even if the result of TEE prompted anticoagulation in up to 1/3 of patients, most of these decisions were not backed by data from randomized controlled trials.…”
Section: How Do You Rule Out Occult Cardiac Sources?mentioning
confidence: 99%
“…Her AF was NVAF, but no thrombus in the cardiac chamber was noted. We then performed transesophageal echocardiography to detect the origin of the embolism, 3) which revealed a ball-like floating thrombus in the LAA. Enhanced computed tomography (CT) scan also illustrated the presence of a thrombus in the LAA and left upper artery without the involvement of other sites ( Fig.…”
Section: Case Reportmentioning
confidence: 99%